Sistem Pakar Diagnosa Gangguan Mesin Mobil - Budianto, Aji; Widodo, Djoko Adi (Jurusan Teknik Elektro Universitas Negeri Semarang, 2018)
The growth of the number of cars in Indonesia each year increases by about 10 to 15 percent. However, this development is not matched by the ability to treat and diagnose the damage. The diagnostic system can make it easy to know what's happening to the machine, providing general solutions and information about how to maintain a car engine. This research developed a machine-failure diagnostic system to predict the damage of car engines. The system development model used is waterfall with stages of analysis (Analysis), design (design), development (Code) and testing (test). The research method used is RnD (Research and Development) with data collection using questionnaires and blackbox test. Experiment test result on content aspect (87,5%), design (93,75%) and usability (78,57%). The results of testing with mechanical car, obtained value 71.67% with the suitability category between symptoms and solutions and general car information. The results show that the waterfall system development model can be used to design the machine damage diagnostic system, RnD research method (Research and Development) can be used in the process of making the system. This study has limitations on some types of cars and does not complement the features provided by the application.